The effect of a learning strategy by playing in the teaching of some basic skills for football game for fifth stage primary pupils - Ali Abbas Hasan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The aim of this research is to prepare and apply an educational curriculum in accordance with the strategy of learning by playing in learning some of the basic skills of football game for fifth grade pupils at the Mukhtar primary school in Maysan province for the academic year 2018-2019. The researcher used the experimental method with pre- and post-test tests for the control and experimental groups. The research community was determined from the fifth stage pupils. 32 pupils were selected as a sample of the research and divided into two groups randomly. The control group became (16) pupils and the experimental group (16) pupils. Moreover, the researcher concluded that this strategy has a positive and effective effect because it provided exciting stimuli and alternatives that gave learners a speed of learning due to the creation of an atmosphere of play fun and thrill, as well as the researcher concluded that this method is better than learning the traditional method. It was recommended that this strategy should be applied to other skills and the rest of the different educational levels in primary schools.